Context and content essays on intentionality in speech and thought - Stalnaker, Robert C.; Oxford eBooks (Oxford : Oxford University Press, 1999)
Robert C. Stalnaker develops a philosophical picture of the nature of speech and thought and the relations between them. He examines how the role that the context in which speech takes place accounts for the way language is used to express thought.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pragmatics; Intentionality (Philosophy); Electronic books